Comparative Analysis of Actual Conditions and Results of Technical Calculations Using Gumbell Method in Mine Dewatering System: A Case Study on Calculation of Rainfall and Runoff Water Discharge - Wahyu Yudha Pangestu; A.A Inung Arie Adnyano; Novandri Kusuma Wardana (CV FOUNDAE, 2023)
This research was conducted at PT. Antareja Mahada Makmur on the mining concession owned by PT. Multi Harapan Utama which is located in Sungai Payang Village, Loa Kulu District, Kutai Kartanegara Regency, East Kalimantan Province. The rainfall data used is for 10 years (2012-2021) which comes from the Dewatering Mining Engineering Department. Data analysis was performed by statistically calculating rainfall data using the Gumbell method to obtain the planned rainfall value. Then the calculation of runoff water discharge is carried out to analyze the existing mine drainage system by comparing the actual conditions and the results of technical calculations. Based on the results of the research for rainfall data for 2012 – 2021, Gumbell's calculations plan to collect rainfall of 94.23 mm/day, rainfall intensity of 14.74 mm/hour with a return period of 5 years and a hydrological risk of 89.26%. The total for the Gumbell method runoff discharge is obtained for runoff water entering the Sump 90 Besar of 2.19 m3/second, runoff water entering the Sump 90 Lorong of 3.03 m3/second, and for water discharge runoff that goes into Sump 100 is 3.68 m3/second. The three open channels in the form of trapezoids and culverts have met the theoretical calculation dimensions, with dimensions that are still able to accommodate and drain runoff water discharge. For three dimensions of the actual sump that is currently smaller than the theoretical calculation of the well volume, the sump capacity calculation obtained a recommended sump volume of 47,045 m3 for a 100 sump, for a sump 90 lorong of 43,012 m3, and for a sump 90 besar of 40,635 m3, with recommended dimension improvements. The operating speed of the pump needs to be increased for the Multiflow MF - 420 pump on a sump 90 lorong from 1159 m3/hour to 1224 m3/hour with an efficiency of 65%, Multiflow MF - 420 pump on a sump 90 besar from 1123 m3/hour to 1269 m3/hour with an efficiency of 70 %, for the Multiflow MF - 420 pump at sump 100 from 1282 m3/hour to 1584 m3/hour with an efficiency of 65%.